Does risk explain persistence in private equity performance? - Buchner, Axel; Mohamed, Abdulkadir; Schwienbacher, Armin (Journal of Corporate Finance, 2016)
In this paper, we investigate whether fund-specific risk helps explain performance persistence in private equity funds, using detailed deal-level cash flow information at both the fund and deal levels. We further extend existing findings to international evidence on buyout and venture capital (VC) by testing the impact of various risk measures. We find that risk is an important driver of performance persistence and helps explain such persistence. We also find persistence in risk in private equity, in particular persistence in downside volatility for both buyout and VC funds. Finally, we document that fund performance is more strongly affected by fund managers able to minimize downside losses than selecting outperforming portfolio companies. This effect is strongest for buyout but, to a weaker extent, also holds for VC. Our results are further robust to controlling for legal factors at the country level.